This Land Is Not For Sale Trust and Transitions in Northern Uganda - Meinert, Lotte; Reynolds Whyte, Susan (Berghahn Books, 2023)
Although violent conflict has declined in northern Uganda, tensions and mistrust concerning land have increased. Residents try to deal with acquisitions by investors and exclusions from forests and wildlife reserves. Land wrangles among neighbours and relatives are widespread. The growing commodification of land challenges ideals of entrustment for future generations. Using extended case studies, collaborating researchers analyze the principles and practices that shape access to land. Contributors examine the multiplicity of land claims, the nature of transactions and the management of conflicts. They show how access to land is governed through intimate relations of gender, generation and belonging.